Investigation of middle school teachers' open-ended question writing skills - Ozturk, Hatice Kumandas (Asian Journal of Education and Training, 2023)
In this study, the skills of middle school teachers to write open-ended questions that measure higher-order mental skills were examined. For this purpose, 18 middle school teachers who worked in Artvin, Turkey and volunteered to participate in the study were asked to write questions. Teachers wrote open-ended questions for a total of 4 courses (Sciences, Mathematics, Turkish, and Social Studies) in accordance with the specified outcomes. In the study designed in the document review pattern of qualitative research methods, questions were analyzed using an evaluation form. As a result of the evaluations, it was observed that teachers were more concerned with the content dimension of the outcomes while writing questions but disregarded the cognitive level of the outcome. It was also found that teachers were inadequate in terms of language and expression in all branches, showed a tendency to copy questions from a source, or could not move away from the question writing style they adopted. However, it was determined that there were especially expression errors, subject-verb agreement problems, and punctuation marks were not used correctly in the questions written.